MODEL KONSERVASI SUMBERDAYA AIR DANAU TOBA - Sihotang, Hotland; Purwanto, M. Yanuar J.; Widiatmaka, Widiatmaka; Basuni, Sambas (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2012)
This study aims to design and build water resource conservation model with emphasis on technical, socio-economical,and ecological aspects involving extensive changes in land use, population growth, continuity of operation of the hydropower of Asahan and some other aspects of the catchment. Illustration of the water balance was made under the influence of land use and other economic activities. Modelling of water balance was constructed by the method of dynamic modeling systems using Powersim software. The water availability was analyzed using FJ.Mock method with variables derived from the analysis of the ecological condition of the catchment area of Lake Toba. The simulations ofwater balance and water level was performed for the condition without intervention variables and with intervention variables. The intervention variables was performed in pessimistic, moderat and optimistic scenario to provide an overview of conservation policy. The simulation of the water balance and lake water level indicate that either in the year of 2017-2057, the best scenario is between moderate and optimistic scenarios in the condition of the population growth between 0.8% - 1.0% per year, infiltration coefficient values between 0.40 to 0.45, the value of land cover factor between 0.25 to 0.3, while the flow ofwater released into the Asahan River of 91.69 m3/sec in average.Keywords: FJ. Mock, water balance, land cover factor value, Lake Toba